An investigation of the relationship of a measure of extraversion-introversion and subsequent recidivism for a selected group of young offenders - Blum, Frank Julius (University of Ottawa (Canada), 1963)
Abstract not available.
Keywords: Psychology, Personality.; Sociology, Criminology and Penology.